Antimicrobial package inserts for veterinary use and public health: a critical analysis and impacts from the residues perspectives (Research, Society and Development, 2020)
The presence of residues in food due to the irrational use of veterinary drugs in farm animals is recognized as a global threat to consumer health, with emphasis on bacterial resistance. Here, we present a comprehensive and not yet reported approach, with the objective of establishing a detailed critical analysis of the instructions for 433 antimicrobials for poultry, cattle and pigs marketed in Brazil, in relation to the current legislation. The frequencies of conformities were compared by the global chi-square test (X2), resulting in 78 contrasts, for each group of data, which were evaluated by approximation to normal (α=0.05). The discrimination between the frequencies was performed by studying the contrasts and by approaching the normal post hoc, using the Bonferroni correlation to estimate the critical z. There was a significant discrepancy between the different requirements (p